Plant Cell Cultures: Biofactories for the Production of Bioactive Compounds - Bapat, Vishwas Anant; Kavi Kishor, Polavarapu Bilhan; Jalaja, Naravula; Jain, Shri Mohan; Penna, Suprasanna (Agronomy (Basel), 2023)
Plants have long been exploited as a sustainable source of food, flavors, agrochemicals, colors, therapeutic proteins, bioactive compounds, and stem cell production. However, plant habitats are being briskly lost due to scores of environmental factors and human disturbances. This necessitates finding a viable alternative technology for the continuous production of compounds that are utilized in food and healthcare. The high-value natural products and bioactive compounds are often challenging to synthesize chemically since they accumulate in meager quantities. The isolation and purification of bioactive compounds from plants is time-consuming, labor-intensive, and involves cumbersome extraction procedures. This demands alternative options, and the plant cell culture system offers easy downstream procedures. Retention of the metabolic cues of natural plants, scale-up facility, use as stem cells in the cosmetics industry, and metabolic engineering (especially the rebuilding of the pathways in microbes) are some of the advantages for the synthesis and accumulation of the targeted metabolites and creation of high yielding cell factories. In this article, we discuss plant cell suspension cultures for the in vitro manipulation and production of plant bioactive compounds. Further, we discuss the new advances in the application of plant cells in the cosmetics and food industry and bioprinting.